106 How do Geriatricians View Their Future Old Age?. (6th February 2020) - Braithwaite, E; Thomas, D; Ninan, S
Abstract: Introduction: Despite, being a specialty intimately acquainted with growing old, there has been little research on how geriatricians view ageing in the terms it might affect themselves in the future. We wished to survey geriatricians as to how they viewed their own futures as they grew older. Methods: We constructed a short survey using survey monkey and sent it to all BGS members, electronically. We also tweeted links to the survey from our personal accounts publicly. Only geriatricians were asked to reply. The survey was open between 25th March and 26th June 2019. Results: 143 people responded to the survey 49% agreed or strongly agreed that they were looking forward to old age 65% agreed or strongly agreed that they were worried about the thought of being frail 70% agreed or strongly agreed that they were worried about developing dementia Despite these responses 89% agreed or strongly agreed that old age will be an enjoyable time of life 76% agreed or strongly agreed that they promoted a positive image of older age to friends and colleagues 85% agreed or strongly agreed that they would be enthusiastic about life in older age 74% agreed or strongly agreed that they looked forward to the social life they would have in older age Themes that arose in the free text responses regarding greatest fears for old age included dependence, physical disability and frailty, dementia, loneliness, bereavement, financial difficulties and the future of society. Respondents hopes for old age included independence and health, enjoying relationships, having more time, and contributing to society. Conclusions: Despite, or perhaps because of, looking after frail older people as part of their profession, geriatricians have mixed feelings towards growing old themselves. Despite most agreeing that old age will be enjoyable, only half of respondents were looking forward to older age. Dementia, dependency and loneliness were common fears for geriatricians. Geriatricians' experience of older age is often in the form of looking after the people who are the frailest of their age group, with the most marked disease burden. Strategies for geriatricians to consider the breadth and variety of old age might come through engagement with the field of medical humanities, reflective practice and spending more time with older people who have less disease burden.